Voltammetric determination of carbaryl in some cereals on an impregnated graphite electrode modified with carbon ink - Gashevskaya, A.S.; Gusar, A.O.; Dorozhko, Ye.V.; Dyorina, K.V.; Kenzhetayeva, S.O. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
Nowadays, pesticides are an integral part of our lives. These compounds are contained in food, water, soil. Consequently people consume them constantly in significant amounts. Therefore, the control of pesticides content in various objects is the most important problem for human health maintaining. In the present work, the electrochemical oxidation of carbaryl on an impregnated graphite electrode modified with carbon ink was studied for the first time. The optimal conditions of carbaryl extraction from some grain crops were selected, followed by its determination on an impregnated graphite electrode modified with carbon ink by linear sweep anodic voltammetry. A number of cereals, such as wheat, oats and corn, were selected as the objects of study. The determination of carbaryl in the objects was carried out after chromatographic separation by TLC. It is revealed that carbon ink increases the electroactive surface of the impregnated graphite electrode. As a result, the sensitivity of carbaryl determination increases. Therefore, the accuracy of carbaryl trace amounts determination increases. The range of linear dependence of dI/dE on the concentration of carbaryl was from 0•10–8 M to 1.6•10–8 M, the detection limit was 1.2•10–9 M.
Кейбір дəнді дақылдарда ерітінді сіңірілген, көміртектік сиялармен модификацияланған, графит электродында карбарилді вольтамперометриялық анықтау
Вольтамперометрическое определение карбарила в некоторых зерновых культурах на импрегнированном графитовом электроде, модифицированном углеродными чернилами
Keywords: carbaryl; linear sweep anodic voltammetry; impregnated graphite electrode; carbon ink; food; pesticides; thin-layer chromatography; crops